Has Medicaid Managed Care Affected Beneficiary Access and Use? - Stephen Zuckerman; Niall Brennan; Alshadye Yemane (SAGE Publishing, 2002)
This paper uses data from the 1997 National Survey of America's Families to examine the effects of the various forms of mandatory Medicaid managed care on access and use among beneficiaries not receiving Supplemental Security Income or Medicare benefits. The results show that mandatory health maintenance organization (HMO) programs have had a positive impact on both children and adults, particularly when compared to Medicaid fee-for-service plans. We observed less dependence on emergency rooms as a usual source of care, a greater probability of visiting a doctor and, for children, greater use of preventive care. In contrast, mandatory primary care case management plans (PCCM) provided some benefits to children, but appeared to have very little impact on adult Medicaid beneficiaries. Mandatory programs that use both HMOs and PCCM produced mixed results. With the exception of mandatory HMO programs, discrepancies in access and use continue to exist between Medicaid managed care enrollees and low-income privately insured people.